Forms of Constructing the Narrative Event in the Stories of( Mohammed Alwan Jabor )Group of ( Socrates' Apple ) As a Model - SALMAN, DR. ABDULRAZZAQ JABBAR (The journal of contemporary issues in business and government, 2020)
The pages of this research are an attempt to study that close relationship which links between the narrative event and time by studying the patterns of building the narrative event in the stories (The Apple of Socrates) by the storyteller (Mohammed Alwan Jabor) . This is due to the exceptional importance of these stories in the course of the short story for the prestigious position that its writer enjoys among the story writers in Iraq Through research . We found that the formats for constructing the narrative event in this collection of stories were organized into only four types with the difference in the proportions of their use by the author from one format to another The writer used (sequential construction) when the narrative events are moving in an ascending line . It is used (overlapping construction) when the narrative events overlap each other . And there is no need to know their chronological sequence . He also used (parallel construction) in those stories that include telling two stories or more at the same time. As for stories that include telling the same event several times and from different points of view where are used repetitive construction This diversity has helped in the use of these methods of building on the storyteller ( Mohammad Alwan Jabor ) access to the field of narrative experimentation from its widest doors .